Wound healing activity of aloe vera extract spray on acute wound in male balb/c mice - Isabella Meliawati Sikumbang; Ratih Arum Astuti; Eka Sakti Wahyuningtyas; Heni Lutfiyati; Ratna Wijayatri; Nasruddin Nasruddin (Universitas Ahmad Dahlan, 2020)
Acute wounds are tissue injuries that are at risk of infection so they require good treatment and care. Aloe vera (Aloe vera L) contains glukomanan compound that are thought to be beneficial in the wound healing process. Spray preparations in the treatment of wounds can provide concentrared content, dry quickly, and easy to use. The purpose of this study was to examine the spray activity of Aloe extract as an acute wound healer in male balb/c mice. This research method is experimental research. The steps that have been carried out include maceration extraction from Aloe vera simplicia powder with 70% ethanol which is then thick extracted in freeze drying to powder extract. Aloe vera spray preparations are made with concentrations of 1%, 3% and 5%. Balb / C mice that had made full thickness acute wounds were divided into 5 treatment groups namely positive control (PC), negative control (NC), F1, F2, and F3. Mice were treated for 14 days then the wound ratio was calculated and analyzed with one way anova test followed by post hoc tukey cramer test. The results showed that the higher of the percentage of Aloe vera extract is the higher of the wound healing activity.Â